Pediatric hanging injury: Rapid intervention and full neurological recovery - Matyas Wondwossen Elssa, MD; Merahi Kefyalew Merahi, MD; Kebron Wossen Aweke, MD; Bement Girma Abera, MD; Kidist Nega Aragaw, MD; Kefelegn Negalign Mekuria, MD; Daniel Berhane Gebresilassie, MD (Radiology Case Reports)
Hanging injuries are a subset of strangulation injuries that pose significant risks of hypoxia and neurological damage, especially in pediatric populations. This report presents a case of a 13-year-old boy with hypoxic brain injury following a suicide attempt by hanging. Key aspects include the prolonged duration of strangulation, absence of vertebral or laryngeal trauma, successful intensive care management, and full recovery without residual neurological deficits. This case emphasizes the importance of timely intervention, multidisciplinary management, and preventive education to address the acute and long-term challenges of pediatric hanging injuries.